Cardiovascular diseases: etiology, prevention, and modern approaches - Asatova Mahliyo Ro’ziqulovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article analyzes cardiovascular diseases, which remain on of the leading causes of mortality worldwide. The causes, main types, and the importance of a healthy lifestyle in their prevention are discussed. Additionally, brief information on diagnostic and treatment methods in modern medicine is provided.